CORRELATION BETWEEN LEVEL OF SOLUBLE FAS AND DEGREE OF SEPSIS SEVERITY BASED ON APACHE II SCORE - Pauline Hadisiswoyo; Endang Retnowati; Erwin Astha Triyono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
A widely used scoring system to assess the severity of sepsis is Acute Physiology, Age, and Chronic Health Evaluation (APACHE) II scoring system, however there are some disadvantages in using this. Other parameters are needed to predict severity and outcome of sepsis. Proinflammatory cytokines and Fas receptors are increased in sepsis and their concentration elevations are correlated with disease severity. An increase of soluble Fas level will follow increasing Fas receptors. This study aimed to prove any correlation between the level of soluble Fas and degree of sepsis severity based on APACHE II score. A cross-sectional observational study was conducted in January-June 2015 on 30 septic patients. APACHE II scores were calculated from the patients’physiological data, age, and chronic health problem status. Levels of soluble Fas were measured using the ELISA method (Human FAS/ CD95 (Factor-Related Apoptosis) ELISA Kit, Elabscience Biotechnology). Levels of soluble Fas ranged between 1,049-2,783 pg/mL (1,855.7 ± 477.27 pg/mL). APACHE II scores varied between 4-29 (17.2 ± 5.82). Significant positive correlations between levels of soluble Fas and APACHE II score (r=0.347, p=0.03) were found. A prediction model of soluble Fas levels based on APACHE II score was made. Linear regression analysis produced a prediction model of soluble Fas levels based on APACHE II score, in which soluble Fas level= 1,365.8 + 28.485 x APACHE II score.